1999
DOI: 10.1002/1529-0131(199902)12:1<52::aid-art9>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an eight-week physical conditioning program on disease signs and symptoms in children with chronic arthritis

Abstract: Objective. To investigate the effects of an 8-week, 24-session weight-bearing physical conditioning program on disease signs and symptoms in children with chronic arthritis.Methods. In a within-subjects, repeated measures design, 25 subjects, ages 8 -17 years, with chronic polyarticular juvenile rheumatoid arthritis (JRA), were assessed at study entry, after an 8-week control period, and after an 8-week exercise period, for 1) disease status, based on joint count (JC) and articular severity index (ASI) (sum of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
64
0
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(72 citation statements)
references
References 27 publications
5
64
0
3
Order By: Relevance
“…Several studies have shown that children with polyarticular JIA are less active than their healthy counterparts and exhibit reduced aerobic and anaerobic exercise capacity (66,67). There is evidence that regular physical conditioning improves joint pain and range of motion in patients with JIA (68,69). A number of reports have suggested that engagement in both low-and high-intensity exercise programs results in improved physical function and decreased pain in patients with JIA (70,71), although a Cochrane meta-analysis of existing randomized controlled trials did not show statistically significant benefits (72).…”
Section: Physical Therapy and Sleep Interventionsmentioning
confidence: 99%
“…Several studies have shown that children with polyarticular JIA are less active than their healthy counterparts and exhibit reduced aerobic and anaerobic exercise capacity (66,67). There is evidence that regular physical conditioning improves joint pain and range of motion in patients with JIA (68,69). A number of reports have suggested that engagement in both low-and high-intensity exercise programs results in improved physical function and decreased pain in patients with JIA (70,71), although a Cochrane meta-analysis of existing randomized controlled trials did not show statistically significant benefits (72).…”
Section: Physical Therapy and Sleep Interventionsmentioning
confidence: 99%
“…Is it safe for patients with JIA to participate in PA? Evidence is accumulating that it is safe, feasible, and acceptable for patients with JIA to participate in PA, exercise programs, and exercise testing (33)(34)(35)(36). To increase their PA, it is unnecessary to increase vigorous PA, which can be difficult for adolescents with JIA.…”
mentioning
confidence: 99%
“…Studies on physical exercise programs in JIA patients show that exercise training is beneficial for this population [5,15,21,[27][28][29][30][31][32][33][34][35][36]. The trends for outcome measures all point to benefits of exercise, with increased strength and range of motion, improved joint stiffness, and better quality of life [37].…”
Section: Clinical Effects Of Exercise In Jia Patientsmentioning
confidence: 99%